Construction of Lyapunov functionals for coupled differential and continuous time difference equations - Mazenc, Frederic; Ito, Hiroshi; Pepe, Pierdomenico (52nd IEEE Conference on Decision and Control, 2013)
A new stability analysis technique for systems composed of a differential equation coupled with a continuous time difference equation is proposed. It is based on the explicit construction of Lyapunov functionals from the knowledge of Lyapunov functions for subsystems. Robustness results of iISS type are inferred from these functionals.